Health and Injury Development in Table Tennis Players: A Literature Review - Ahady, Muhammad Yan; Sembiring, Anggun Amalia; Hutagaol, Khairunnisa; Hawari, Mahran; Ramadhani, Arif (Journal Coaching Education Sports, 2024)
Athletes' and coaches' lack of knowledge about health and injury progression is also a major factor in the occurrence of injuries among table tennis athletes. The purpose of this study was to identify common injury patterns, risk factors that influence injury progression, and effective injury prevention and management strategies. The method of this study was a literature review regarding the development of health and injuries in table tennis players obtained from sciencedirect, Eric, and Google Schoolar. Data analysis techniques were conducted by citing studies from around the world, identifying common injury patterns, risk factors that influence injury development, and effective injury prevention and management strategies. Key findings highlighted the importance of a holistic approach that encompasses physical, mental and social aspects in maintaining optimal health and performance for table tennis athletes. This study also emphasizes the need for integration of recent findings in research to support innovation in injury prevention strategies.